Interferensi bahasa Indonesia ke dalam bahasa Inggris pada abstrak jurnal ilmiah - Budiarti, Any (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This research aims not only to discuss the interference of the Indonesian language into English as reflected in scientific journal abstracts but also to describe the types of such interference. Thirteen scientific journals were examined in this study. The method applied was descriptive, employing distributional and similarity analyses. The data were collected from scientific journal abstracts published between 2003 and 2008. The results indicate three types of interference: morphological, syntactic, and semantic. Morphological interference occurs in verb forms for the third person singular, plural forms, and possessives. Syntactic interference includes ill-formed phrases, passive voice constructions, parallelism errors, and the omission of to be and articles. Semantic interference consists of addition and substitution.